Determinants of felt demand for dengue vaccines in the North Caribbean region of Colombia - Yalil T. Bracho-Churio; Ruth A. Martínez-Vega; Alfonso J. Rodriguez-Morales; Ronald G. Díaz-Quijano; María L. Luna-González; Fredi A. Diaz-Quijano (BMC, 2017)
Abstract Background The increasing burden associated with dengue in Latin America makes it essential to understand the community's interest in acquiring vaccines, as an input to plan its introduction in endemic regions. The objective of this study is to learn the felt demand for dengue vaccines by estimating the willingness to pay and its associated factors in endemic communities of the North Caribbean region of Colombia. Methods A population survey was administered from October to December 2015, including 1037 families in 11 municipalities in Colombia. One adult per family was interviewed on their perception and history of dengue. Participants received a description of four hypothetical scenarios of dengue vaccines, administered in a single dose or in 3 doses, with an effectiveness of 70% for 5 years or 95% for 30 years. The willingness to pay for each one of these vaccines was inquired vs. 5 hypothetical prices in Colombian pesos. Results Most participants recognized dengue as a serious disease in children (99.3%) and adults (98.6%). 33 (3.2%) of the total respondents reported having suffered dengue and 19 (57.6%) of them required hospitalization. The price of the vaccine was inversely related to the willingness to pay. In addition, single dose vaccines (compared to 3 doses) and one with a protection of 95% for 30 years (compared to an effectiveness of 70% for 5 years), were associated with greater willingness to pay. Greater willingness to pay was observed among the respondents who considered it likely to get the disease, either themselves (OR 1.56; CI 95% 1.08-2.26) or their children (OR 1.89; CI 95% 1.28-2.81), in the next 5 years. The participants who have been diagnosed with dengue also showed greater willingness to pay (OR 1.89; CI 95% 1.01-3.54) compared to those who did not have this history. Conclusion Factors such as price, number of doses and effectiveness can independently influence the decision to purchase a vaccine against an endemic disease, such as dengue. Additionally, this study reveals that background and perceptions of the disease can affect individuals' interest in acquiring this type of preventive interventions.